Decontamination of ibuprofen micropollutants from water based on visible-light-responsive hybrid photocatalyst. Issue 2 (April 2022) - Liu, Hong; Nkundabose, Jean Paul; Chen, Houwang; Yang, Liuliu; Meng, Chen; Ding, Ning
Abstract: Heterogeneous photocatalysis has caught attention in scientific community as an alternative and sustainable approach for environmental remediation. With that said, it is still a challenge to find affordable, photostable, harmless and chemically inert catalysts. In the present study, a novel visible light-responsive hybrid photocatalyst (AgBr/PSGCN-100) was synthesized via in-situ deposition precipitation that combines the phosphorus and sulfur co-doped graphitic carbon nitride (PSGCN) and AgBr particles. The as-synthesized samples were successfully characterized by various techniques including XRD, FT-IR, SEM, TEM, XPS, UV–vis DRS and PL. Compared to the other as-prepared samples and single photocatalysts, AgBr/PSGCN-100 performed well in terms of IBF photodegradation. Using 0.1 g AgBr/PSGCN-100, 0.5 mg/l, 1 mg/l, and 5 mg/l of IBF were completely degraded just in 20, 30, and less than 60 min of visible light irradiation, respectively; whereas 90% efficiency was achieved with increased IBF concentration (15 mg/L) in 100 min. As per trapping scavenger studies, the holes (h + ) and superoxide radicals (O2 − ) were the predominant reactive oxygen species for IBF degradation. However, hydroxyl radicals (OH) also played a significant role. The good photocatalytic performance of AgBr/PSGCN-100 was linked to its heterostructure form. IBF intermediate products were analyzed by LC/MS-MS used negative electrospray ionization mode (ESI). We believe this study to be insightful in the rational design and best conception of heterostructure photocatalysts for environmental applications. Graphical Abstract: ga1 Highlights: A hybrid heterojunction photocatalyst AgBr/PSGCN-100 was synthesized. AgBr/PSGCN-100 showed efficient degradation performance over Iburofen. O2− along with h+ and OH played significant roles in Iburofen degradation. The probable degradation pathways of IBF were addressed.